2018
DOI: 10.1099/ijsem.0.003020
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paragasseri sp. nov., a sister taxon of Lactobacillus gasseri, based on whole-genome sequence analyses

Abstract: Three strains, JCM 5343, JCM 5344 and JCM 1130, currently identified as Lactobacillus gasseri, were investigated using a polyphasic taxonomic approach. Although these strains shared high 16S rRNA gene sequence similarities with L. gasseri ATCC 33323 (99.9 %), they formed a clade clearly distinct from ATCC 33323 based on whole-genome relatedness. The average nucleotide identity and in silico DNA-DNA hybridization values of these three strains compared to L. gasseri ATCC 33323 were 93.4-93.7 and 53.1-54.1 %, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 24 publications
5
42
0
Order By: Relevance
“…Seventy-nine strains were determined as L. paragasseri, and the remained 13 (14%) strains were L. gasseri, revealing that the most (86%) of isolates initially identified as L. gasseri by 16S rDNA sequencing were L. paragasseri. The current results were highly in line with previous publication by Tanizawa and colleagues [16], in which they reported that a large portion of genomes currently labelled as L. gasseri in the public database should be re-classified as L. paragasseri based on whole-genome sequence analyses as well. All those results indicated that L. gasseri and L. paragesseri are sister taxon with high similarity but not the same species, and the cultivable "L. gasseri" isolated from environment actually contained both L. gasseri and L. paragasseri species, which might be the reason for the high intraspecies diversity among "L. gasseri" exhibited.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Seventy-nine strains were determined as L. paragasseri, and the remained 13 (14%) strains were L. gasseri, revealing that the most (86%) of isolates initially identified as L. gasseri by 16S rDNA sequencing were L. paragasseri. The current results were highly in line with previous publication by Tanizawa and colleagues [16], in which they reported that a large portion of genomes currently labelled as L. gasseri in the public database should be re-classified as L. paragasseri based on whole-genome sequence analyses as well. All those results indicated that L. gasseri and L. paragesseri are sister taxon with high similarity but not the same species, and the cultivable "L. gasseri" isolated from environment actually contained both L. gasseri and L. paragasseri species, which might be the reason for the high intraspecies diversity among "L. gasseri" exhibited.…”
Section: Discussionsupporting
confidence: 92%
“…All of the 94 strains were classified into two groups, with 80 strains including L. paragasseri K7 (as type L. paragasseri strain) showing an ANI value range 97-99%, and the other group consisted of 14 strains including the type strain L. gasseri ATCC 33323 (as type L. gasseri strain) with an ANI range 93-94% compared with L. paragasseri. According to a previous report, L. gasseri K7 was reclassified as L. paragasseri based on whole-genome analyses [16], therefore, other 79 strains on the same group with L. paragasseri K7 were preliminarily identified as L. paragasseri, while the remained 13 strains on the other branch with L. gasseri ATCC33323 were identified as L. gasseri.…”
Section: Ani Valuesmentioning
confidence: 98%
See 2 more Smart Citations
“…In samples that had both a 16S and GTDB taxonomic classification, there was disagreement in 154 out of 1,467 samples. Of these, 47% were accounted for by the recently described L. paragasseri (95) (n=72). This possibly highlights a lag in the reclassification of assemblies in the NCBI Assembly database.…”
Section: Use Case: the Lactobacillus Genusmentioning
confidence: 99%